2016
DOI: 10.1093/heapol/czv124
|View full text |Cite
|
Sign up to set email alerts
|

District decision-making for health in low-income settings: a systematic literature review

Abstract: Health management information systems (HMIS) produce large amounts of data about health service provision and population health, and provide opportunities for data-based decision-making in decentralized health systems. Yet the data are little-used locally. A well-defined approach to district-level decision-making using health data would help better meet the needs of the local population. In this second of four papers on district decision-making for health in low-income settings, our aim was to explore ways in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
115
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(118 citation statements)
references
References 41 publications
1
115
0
2
Order By: Relevance
“…The purpose of data use and its impact on data producers influenced how the data were shared and used. Another systematic review concluded that quality and availability of health and facility data, human dynamics, and financial constraints were the key challenges to district‐level decision making in LMICs …”
Section: Resultsmentioning
confidence: 99%
“…The purpose of data use and its impact on data producers influenced how the data were shared and used. Another systematic review concluded that quality and availability of health and facility data, human dynamics, and financial constraints were the key challenges to district‐level decision making in LMICs …”
Section: Resultsmentioning
confidence: 99%
“…Other qualitative studies in district health‐care systems in low‐income countries explored the attitude of mothers' toward utilization of maternal health services, decision‐making process, and data platforms for decision‐making …”
Section: Discussionmentioning
confidence: 99%
“…Also, we confirm what Vargas et al, 21 had already mentioned: that the formation of health networks was based more in negotiations between the interested parties than in the proper planning. Wickremasinghe et al 22 noticied that for the low income Countries, the data from the information systems on health management were not widely used for decisions making, sometimes because there was a standardized process for their use or because they were poor quality.…”
Section: Discussionmentioning
confidence: 99%